Evaluasi Produksi Perikanan Budidaya di Kabupaten Kediri Jawa Timur - Hakim, Riza Rahman; Effendi, Irzal (JAGO TOLIS : Jurnal Agrokompleks Tolis, 2024)
Aquaculture is one of the priorities of the Ministry of Maritime Affairs and Fisheries (KKP) in developing blue economy policies in Indonesia. Kediri Regency, the center of aquaculture production in East Java, plays a pivotal role in the production of fresh water-cultivated fish not only for consumption but also for ornament. Proper evaluation in relation with the aquaculture production in Kediri is so limited; even though, it is fundamental for setting the best recommendation for the future strategy of aquaculture production up. Hence, the aim of this research is to evaluate aquaculture production in Kediri Regency and to recommend its future development strategy. This study used descriptive methods. The data used is secondary data with the main data sources from BPS KKP and Kediri Regency. Afterwards data were analyzed by describing them qualitatively. Results showed that the development of aquaculture in Kediri Regency was going well. This can be seen from the increase of aquaculture production both in volume and in value during 2019-2022. Recommendations related policy strategy for the future aquaculture production can be implemented by increasing the abilities and skills of fish farmers; improving the quality of counseling and training on the dissemination of aquaculture technology; enhancing infrastructure and facilities, especially public facilities; conducting post-harvest and fish processing training to increase added value of fish products; developing an integrated information system between farmers in each sub-district, which is led by the Fisheries Agency in Kediri Regency; last but not least, strengthening collaboration with universities in order to disseminate research results to the fish cultivating community.